Total quality management : - George, Stephen (Wiley, 1994)
Creating a "best practices" guide which explains how to incorporate quality systems into any company, this text tackles the problems of improving profitability, managing people, helping customers, developing a strategic plan and designing quality into products, services and processes. The "Portable MBA" series has been developed to cover the range of business functions in a typical MBA course. Each book offers practical, readable overviews of insights and information needed for the MBA programmes.